The Relationship Between Daily Dietary Habits of the Elderly and Increased Blood Sugar Levels in Diabetes Mellitus at the Sukabumi Buay Bahuga Way Kanan Community Health Center - Solpani, Tya; Agata, Annisa; Subardiah, Ida (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
The primary causes of diabetes are genetic factors and an unhealthy lifestyle. Many other factors also influence diabetes, such as social environment and use of healthcare services. Diabetes is a chronic disease that does not immediately cause death, but can have serious consequences if left untreated. One cause of increased blood sugar levels is dietary habits. The purpose of this study was to determine the relationship between daily dietary habits and the increased blood sugar levels of the elderly at the Sukabumi Buay Bahuga Way Kanan Community Health Center. This study was a quantitative analytical study with a cross-sectional design. The population was all 181 elderly people aged 60 years and older registered at the Sukabumi Buay Bahuga Way Kanan Community Health Center, resulting in a sample size of 124. The sampling technique used in this study was purposive sampling. Based on the results of univariate analysis, it is known that most respondents have normal blood sugar levels amounting to 65 respondents (52.4%) and most respondents have bad eating habits amounting to 70 respondents (56.5%). Based on the results of statistical tests, a p-value of 0.001 or p-value <0.05 or Ha is accepted, which means there is a Relationship Between Daily Eating Habits and Increased Blood Sugar Levels in Elderly People with Diabetes Mellitus at the Sukabumi Buay Bahuga Way Kanan Health Center. This research can increase awareness, access, and quality of health services, as well as empower the elderly to play an active role in maintaining their own health.